Ratio of Diverging Series'!

Calculus Level 5

P = n = 1 3 + 4 + 5 + + ( n terms ) 1 3 5 + 2 4 6 + 3 5 7 + + ( n terms ) \mathcal P=\sum_{n=1}^{\infty}\dfrac{3+4+5+\cdots+(\text{n terms})}{1\cdot 3\cdot 5+2\cdot 4\cdot 6+3\cdot 5\cdot 7+\cdots +(\text{n terms})}

If the value of P \mathcal P can be written in the form A B \color{#D61F06}{\dfrac AB} , where A A and B B are coprime positive integers , find A + B + 5 \sqrt{\color{#D61F06}{A}+\color{#D61F06}{B}+5} .

10 The series diverges 3 None of the other options 4 2016 6 5

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rishabh Jain
Jul 22, 2016

P = n = 1 [ r = 1 n ( r + 2 ) r = 1 n r ( r + 2 ) ( r + 4 ) ] \mathcal P=\displaystyle\sum_{n=1}^{\infty}\left[\dfrac{\displaystyle\sum_{r=1}^{n}( r+2)}{\displaystyle\sum_{r=1}^n r(r+2)(r+4)}\right]

Numerator is a sum of an arithmetic progression which is: n 2 ( 2 3 + ( n 1 ) 1 ) = n ( n + 5 ) 2 \small{\dfrac n2(2\cdot 3+(n-1)1)=\dfrac{n(n+5)}2} .

While denominator ( ) (\color{#3D99F6}{**}) can be written as:

r = 1 n ( r 3 + 6 r 2 + 8 r ) \sum_{r=1}^{n}(r^3+6r^2+8r)

Use r = n ( n + 1 ) 2 , r 2 = n ( n + 1 ) ( 2 n + 1 ) 6 , r 3 = n 2 ( n + 1 ) 2 4 \small{\color{#20A900}{\sum r=\dfrac{n(n+1)}2,\sum r^2=\dfrac{n(n+1)(2n+1)}6,\sum r^3=\dfrac{n^2(n+1)^2}4}}

so that denominator simplifies to :

n 2 ( n + 1 ) 2 4 + n ( n + 1 ) ( 2 n + 1 ) + 4 n ( n + 1 ) \dfrac{n^2(n+1)^2}{4}+n(n+1)(2n+1)+4n(n+1)

= n ( n + 1 ) ( n + 4 ) ( n + 5 ) 4 =\dfrac{n(n+1)(n+4)(n+5)}{4}

P = n = 1 n ( n + 5 ) 2 n ( n + 1 ) ( n + 4 ) ( n + 5 ) 4 2 \therefore \mathcal P=\displaystyle\sum_{n=1}^{\infty}\dfrac{\cancel{\color{#D61F06}{\dfrac{n(n+5)}2}}}{\dfrac{\cancel{\color{#D61F06}{n}}(n+1)(n+4)\cancel{\color{#D61F06}{(n+5)}}}{\cancelto2{\color{#D61F06}{4}}}}

= n = 1 2 ( n + 1 ) ( n + 4 ) = 2 3 n = 1 ( 1 n + 1 1 n + 4 ) =\displaystyle\sum_{n=1}^{\infty}\dfrac{2}{(n+1)(n+4)}=\dfrac 23\displaystyle\sum_{n=1}^{\infty}\left(\dfrac{1}{n+1}-\dfrac{1}{n+4}\right)

( A T e l e s c o p i c S e r i e s ) \large (\color{#3D99F6}{ \mathbf{A~Telescopic~Series}})

= 2 3 ( 1 2 + 1 3 + 1 4 ) \large =\dfrac 23\left(\dfrac 12+\dfrac 13+\dfrac 14\right)

= 13 18 =\large \dfrac{13}{18}

13 + 18 + 5 = 6 \large\therefore \sqrt{13+18+5}=\boxed{\color{#007fff}{6}}


( ) (\color{#3D99F6}{**}) When denominator can alternately be solved using Telescopic Series also.

1 8 r = 1 n { ( ( r + 6 ) ( r 2 ) ) ( r + 4 ) ( r + 2 ) ( r ) } \dfrac 18\sum_{r=1}^n\left\{((r+6)-(r-2))(r+4)(r+2)(r)\right\}

= 1 8 [ r = 1 n { ( r + 6 ) ( r + 4 ) ( r + 2 ) ( r ) } { ( r + 4 ) ( r + 2 ) ( r ) ( r 2 ) } ] = \dfrac 18\left[\sum_{r=1}^n\left\{(r+6)(r+4)(r+2)(r)\right\}-\left\{(r+4)(r+2)(r)(r-2)\right\}\right]

( A Telescopic series ) (\textbf{A Telescopic series})

Which gives the same result as above.

Used exactly the same approach just for evaluating series in denominator i used telescopic series instead of directly using summation formula . for that just multiply and divide general term by 8 and write it (n+6)-(n-2) which will lead to telescopic series

Prakhar Bindal - 4 years, 10 months ago

Log in to reply

Nice.. I've added it :-)

Rishabh Jain - 4 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...